REDESCUBRIMIENTO DE UNA ESPECIE DE CALCEOLARIA (CALCEOLARIACEAE) REDISCOVERY OF A CALCEOLARIA SPECIES (CALCEOLARIACEAE) - Mélica Muñoz-Schick (Universidad de Concepción, 2008)
The species Calceolaria reicheana, nomen nudum, was rediscovered in the Metropolitan Region, Chile. It is considered as a valid species, described and renamed as Calceolaria espinosae. A new locality is also recorded.